Corrigendum to "On a quasilinear elliptic problem with convection term and nonlinear boundary condition" [Nonlinear Anal. 187 (2019) 159–169]. (December 2019) - Marano, Salvatore A.; Winkert, Patrick
Abstract: We correct the proof of Theorem 4.6 in "On a quasilinear elliptic problem with convection term and nonlinear boundary condition" [Nonlinear Anal. 187 (2019) 159–169].